The Role of School Principal in Improving Education Quality at Smp Negeri 1 Manado - Bagensa, Christian; Lumapow, Harol R.; Mongdong , Romi J. (Indonesian Journal of Multidisciplinary Science, 2025)
This study aims to comprehensively describe the role of school principals in improving the quality of education at SMP Negeri 1 Manado which includes functions as educators, administrators, supervisors, leaders, innovators, and motivators. The research approach used is qualitative descriptive, with data collection techniques through in-depth interviews, observations, and documentation of school principals, vice principals, teachers, and administrative staff. Data analysis is carried out through three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study show that school principals play an active role in improving the quality of education through various aspects of leadership. As educators, school principals provide examples, facilitate teacher training, and encourage the use of technology in learning. As administrators, principals are able to design, organize, direct, and evaluate school programs efficiently through the digitization of administration. In the role of supervisor, the principal carries out academic supervision regularly to ensure that the learning process runs effectively. As a leader, the principal displays transformational leadership by building a collaborative culture and open communication. In the role of innovator, the principal develops various technology-based innovations such as student discipline applications and the use of digital media in learning, which has been proven to significantly reduce the number of disciplinary violations. Meanwhile, as a motivator, the principal fosters the work spirit of teachers and students through awards, appreciation, and continuous support.